Kontrol diri dan kecenderungan agresivitas verbal di media sosial pada remaja - Nugrahani, Elisa Retno; Matulessy, Andik; Pratitis, Nindia (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2024)
Adolescence is a period in which adolescents experience a process of self-development, both psychologically and physically. It is the phase where they have to be ready to enter adulthood, requiring them to prepare mentally and physically. The low levels of self-control cause individuals to tend to take risks and violate the rules without considering the long-term consequences, which will lead to a verbal aggressiveness tendency on social media. This study aims to determine the relationship between self-control and verbal aggression tendencies in social media among adolescents. For a total of 165 participants, this study was conducted at SMAIT- Al-Uswah Surabaya with the specified requirements for inclusion involving adolescents between the ages of 15-18 years who were actively using social media. Based on Spearman’s rho calculation in this study, a correlation coefficient value of -0,533 was identified, with a p-value of 0,000 (p<0,01). According to the result, there is an extremely significant relationship between self-control and verbal aggressiveness in adolescents. Masa remaja merupakan periode di mana para remaja mengalami proses perkembangan diri, baik dari segi psikis maupun fisik. Hal ini fase di mana mereka harus bersiap-siap untuk memasuki masa dewasa mengharuskan mempersiapkan mental dan fisik yang matang. Rendahnya tingkat kontrol diri menyebabkan individu cenderung lebih suka mengambil risiko dan melanggar peraturan tanpa mempertimbangkan konsekuensi jangka Panjang yang akan menimbulkan kecenderungan agresivitas verbal di media sosial. Penelitian ini memiliki tujuan mengetahui hubungan antara kontrol diri dengan kecenderungan agresivitas verbal di media sosial pada remaja. Penelitian ini dilakukan di SMAIT- Al-Uswah Surabaya dengan jumlah partisipan 165 siswa, kriteria yang dibutuhkan yaitu ramaja berusia 15-18 tahun, dan aktif dalam bersosial media. Berdasarkan hasil perhitungan spearman’s rho didapatkan nilai correlation coefisient sebesar -0,533 dengan nilai p=0,000 (p<0,01). Menurut hasil tersebut berarti ada hubungan yang sangat signifikan antara kontrol diri dengan kecenderungan agresivitas verbal pada remaja.